If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -17u + 71 = 12u + 42 Reorder the terms: 71 + -17u = 12u + 42 Reorder the terms: 71 + -17u = 42 + 12u Solving 71 + -17u = 42 + 12u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-12u' to each side of the equation. 71 + -17u + -12u = 42 + 12u + -12u Combine like terms: -17u + -12u = -29u 71 + -29u = 42 + 12u + -12u Combine like terms: 12u + -12u = 0 71 + -29u = 42 + 0 71 + -29u = 42 Add '-71' to each side of the equation. 71 + -71 + -29u = 42 + -71 Combine like terms: 71 + -71 = 0 0 + -29u = 42 + -71 -29u = 42 + -71 Combine like terms: 42 + -71 = -29 -29u = -29 Divide each side by '-29'. u = 1 Simplifying u = 1
| (-7n-18)*5-3=12 | | 4a-3a(a-2)=6a-4 | | (3v+7)(5-v)=0 | | 22x+96=22x+59 | | 2x-6a=10forx | | 2a+5b=-4 | | 3[x-4(x-2)]-6=-4-7 | | dy(x+y-6)=dx(x+y+4) | | 4=(1n-2n)+5*5 | | (6n-3)2=3(4n+7) | | 3x+x+1=8x-4+1 | | 5x-7(2+3x)=x+20 | | X=-12-(-6) | | -8u+6(u-2)=8 | | 4u-5=-13 | | x-(6)=12 | | -17+x=-20 | | 6y=0.2+1.2y-1 | | 17+x=-20 | | 1-1z=8 | | -3(19q-10)=-6(-6+9q) | | 0.68n-3+0.25n=1.75 | | 2(-12-y)-3y=6 | | 2x+6a=10 | | 1-1x=8 | | C=2(pi)20 | | -4f(x)=4x^2-3x | | -3.5a-11.4+9.9=3 | | -7.8p-6.6p=-7.2 | | C=2(pi)16 | | 2+3+1-4=a | | 2y+10+7x=0 |